Rehabilitation Medicine Faces Living Wills, Advance Directives, and Quality of Life Issues for the Elderly and Persons with Disabilities - Anderson, J. Michael (Journal of religion in disability & rehabilitation, 1994)
This article is a substantive exploration of the Patient Self-Determination Act as it applies to the delivery of rehabilitation services. The Act itself is designed to provide patients with greater control over their medical care and protection against inappropriate, intrusive care during the last days of life. Less visible are other underlying agendas from various interest groups, with their concerns about cost containment, euthanasia, right to die, and quality of life issues. These agendas raise moral and ethical problems particularly for Physical Medicine and Rehabilitation (PM&R) physicians, as those patients were most clearly affected by the legislation are frequently those persons whom we serve. Specific historical examples are cited which remind of the dangers arising from reliance on cost-effectiveness and the pragmatic, utilitarian viewpoint as the basis for provision of medical care. Our response to these considerations will impact not only the course of health care delivery in this country, but will also affect society's valuation and care of individuals who experience chronic disability.